AKUNTANSI PENGHIMPUN DANA DALAM PERSPEKTIF ISLAM - Rusmini, Rusmini; Hamdi, Muhammad; H.S, Dovi Iwan Musthofa (LAN TABUR : Jurnal Ekonomi Syariah, 2024)
Fundraising accounting is a specialized area in accounting that is concerned with collecting and managing funds from various sources for specific purposes, such as non-profit organizations, foundations, investment companies, and charitable projects. The concept and implementation of fundraising accounting is important in measuring financial performance, meeting legal requirements, and meeting the expectations of shareholders, donors, and regulators. This study outlines the basic concepts in accounting for raising funds, including identifying sources of funds, managing funds, and allocating funds in accordance with organizational goals. We also discuss relevant basic accounting principles, such as recordkeeping, revenue recognition, and measurement of assets and liabilities. In addition, we explain the various reporting methods and metrics used to measure fundraising success. The importance of proper implementation in fundraising accounting is also emphasized in this study. Effective implementation involves accurate record-keeping processes, segregation of funds, and maintenance of transparent financial information. We also discuss challenges that are often faced in fundraising accounting, such as changes in regulatory rules, complexity of funding sources, and measuring social impact. Finally, this study emphasizes the importance of openness and transparency in fund raisers' financial reporting, which can build trust with shareholders, donors and other interested parties. Good fundraising accounting can help organizations achieve their financial and social goals while ensuring proper accountability in the management of funds provided by the community. Keywords: Accounting, Fundraising, Islamic perspective